Balanced Scorecard as a Performance Measurement System in Malaysian Private Institutions of Higher Learning: Empirical Findings - Hafiz bin Rosli, Mohamad; Fawzia binti Md Ariff, Farrah; binti Said, Jamaliah (International Journal of Engineering and Technology, 2018)
Balanced Scorecard (BSC) is a well-known performance measurement tools and some researchers have highlighted its relevance to Institutions of Higher Learning (IHL). In order to response to the globalization phenomenon today, IHL must adopt the most suitable tool such as Performance Measurement System (PMS) in assessing academicians’ performance. The adoption of Strategic Performance Measurement System (SPMS), proven to realize significant cost saving, improve personal satisfactions and enhance organizational performances based on previous studies. Therefore, the objective of this paper is to determine the relationship between leadership, communication and academic qualification towards the adoption of BSC. Data were collected quantitatively through a survey questionnaire with the usable response rate of 78.57%. The descriptive results of this study revealed that the majority of academicians’ extensively agrees that the measurement used in the BSC are effective in assessing academicians’ performances. This finding also reveals that leadership, communication and academic qualification were significantly influenced the adoption of BSC. The findings from this study have advanced the literature on BSC especially in the education sector. It also provides a better understanding of BSC as the performance measurement tool in assessing academicians’ performance.